Uncoupled poroelastic and intrinsic viscoelastic dissipation in cartilage. (August 2018) - Han, Guebum; Hess, Cole; Eriten, Melih; Henak, Corinne R.
Abstract: This paper studies uncoupled poroelastic (flow-dependent) and intrinsic viscoelastic (flow-independent) energy dissipation mechanisms via their dependence on characteristic lengths to understand the root of cartilage's broadband dissipation behavior. Phase shift and dynamic modulus were measured from dynamic microindentation tests conducted on hydrated cartilage at different contact radii, as well as on dehydrated cartilage. Cartilage weight and thickness were recorded during dehydration. Phase shifts revealed poroelastic- and viscoelastic-dominant dissipation regimes in hydrated cartilage. Specifically, phase shift at a relatively small radius was governed by poroviscoelasticity, while phase shift at a relatively large radius was dominantly governed by intrinsic viscoelasticity. The uncoupled dissipation mechanisms demonstrated that intrinsic viscoelastic dissipation provided sustained broadband dissipation for all length scales, and additional poroelastic dissipation increased total dissipation at small length scales. Dehydration decreased intrinsic viscoelastic dissipation of cartilage. The findings demonstrated a possibility to measure poroelastic and intrinsic viscoelastic properties of cartilage at similar microscale lengths. Also they encouraged development of broadband cartilage like-dampers and provided important design parameters to maximize their performance. Graphical abstract: fx1 Highlights: Poroelasticity and intrinsic viscoelasticity were decoupled. Poroelasticity increased dissipation over baseline intrinsic viscoelasticity. Cartilage energy dissipation was superior to isotropic poroelastic materials. Substantial loss of fluid decreased intrinsic viscoelasticity. Poroelastic and viscoelastic properties were measured at microscale lengths.